Biometria, crescimento inicial e diversidade genética em mangabeira - Soares, Adrielle Naiana Ribeiro (2018)
The mangabeira (Hancornia speciosa Gomes) is a fruit species that is native to Brazil. In the State of Sergipe, the mangabeira has a social, cultural and economic importance. The fragmentation of the natural areas of the species has intensified and in this context, the Mangaba Genebank (BAG Mangaba) was implemented. The two specific research investigations of this work were carried out at the Embrapa Coastal Tablelands and at the University of Florida, USA, in order to evaluate the various aspects concerning the propagation and the genetic diversity of the species. In the first experiment, the propagation and the biometrics of the fruits and seeds of the BAG Mangaba accessions were evaluated. In the biometric studies, the weight and the dimensions (length, width and thickness) of fruits and seeds were evaluated, as well as the number of seeds per fruit. The propagation analyzes and the experimental design were completely randomized, with 4 replicates of 25 seeds, totaling 100 seeds per treatment. In this study, the seeds were sown in polyethylene bags that contained sand as a substrate. They were then submitted to the following determinations: emergence (E%), emergency speed indexes (ESI), seedling heights (cm), diameters (DIA) and the percentages of survival (S%), together with the fruit and seed biometrics (weight, length and width, together with the thickness of the fruits and seeds, as well as the number of seeds per fruit). The second study was conducted at the University of Florida, USA, with the objective of evaluating the genetic diversities of the accessions and the progenies of the mangaba fruit, by using microsatellite markers (SSR). A total of 96 samples were used, 9 matrices and 87 progenies. The genetic diversities were measured by using the following genetic parameters: the allele numbers (N), the allelic richness (R), the expected heterozygosity (He), the observed (Ho) genetic divergence indexes (Fst), the endogamy coefficients (f), Nei’s genetic identities (GI), the parental relationship between the progenies and the matrices, as well as the means of the clusters, conducted by Bayesian analyzes. In a third experiment, the researchers calculated the genetic diversities of 155 individuals from 10 natural populations of mangabeira in the State of Sergipe, by using ISSR markers. The genetic diversities were measured as a result of the following parameters: the polymorphism percentages, the coefficients of variation, Shannon’s indices (I), the expected heterozygosities (He), the similarity among the individuals, the UPGMA groupings, the principal coordinate analyzes (PCoA), as well as by using AMOVA. The accessions showed divergences regarding their biometric characteristics and there was a significant asymmetry between the progenies in their propagative variables, highlighting the progeny accessions from the States of Pará (ABP1, ABP2 and ABP4), Sergipe (PTP1, PTP2, TCP2 and TCP6) and Bahia (LGP1, LGP3, LGP4 and BIP2). For the molecular analyzes, it was verified that the SSR markers showed a moderate genetic variability between the progenies and the matrices, with the progenies from the accessions in the State of Pará (ABP1 and ABP2) being the most divergent. In the natural populations of Sergipe, when making the use of the ISSR markers, a high polymorphism rate (100%) and the formation of five large groups were observed. The mangabeira is a species that is still in the stage of domestication and studies that involve their propagation, their morphology and their genetic diversities are important for the development of strategies for the conservation and the selection of plants, with characteristics of interest in various breeding programs.